EFEKTIVITAS PERMAINAN ARRANGE ALPHA TERHADAP KEMAMPUAN KONSEP MENGENAL HURUF DAN MERANGKAI KATA DALAM BAHASA INGGRIS PADA SISWA TK AL-HIDAYAH KEBONSARI TENGAH - Dzulkifli, Dzulkifli; arumsari, andini dwi (MOTORIC, 2023)
Arrange Alpha is an educational game tool designed and created with the aim of simplifying and streamlining the learning process in recognizing letters and word arrangements in English so that it not only makes students understand pronunciation in English but also so that students can understand spelling and wording in English. In this study, the research method used is a Experimental method. With the learning method used is the experiential learning method. This research was conducted at Al-Hidayah Kebonsari Tengah Kindergarten for 2 meetings, with the subjects of group B kindergarten students with a total of 17 children. With the results in the first experiment conducted by researchers most of the children who came forward had difficulty in composing words and did not conform to spelling. After the learning and recognition in the second experiment, more students and students have succeeded perfectly in compiling the given words. Keywords: An educational game tool, recognizing letters and stringing words in English